PERSEPSI PEMBACA TERHADAP PEMBERITAAN “MK TOLAK LEGALISASI GANJA MEDIS UNTUK KESEHATAN!” DI PORTAL BERITA DETIKCOM - Ramadhan Sigih Pratama; Tiara Puspanidra; Ratih Siti Aminah (UNIVERSITAS PAKUAN, 2023)
We already know that technology has become more sophisticated over time, resulting in progress and novelty in many sectors, the mass media industry being one of them. Technological developments have not failed to influence the world of journalism today, the mass media industry is increasingly sophisticated and has easy access for readers, so that news from abroad can be easily read by Indonesian people today. For example, news about the legalization of marijuana in Thailand has sparked discussion in Indonesia, so researchers want to conduct research on readers' perceptions regarding news about the rejection of legalization of marijuana in Indonesia. This research aims to find out how the news is exposed, what is the perception of the news